Comparative Study of Islamic and Secular Economic Law in Nigeria: Implications for Policy Making - Abdullahi Oyelekan Maruf (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This comparative study explores the coexistence of Islamic and secular economic laws in Nigeria and their implications for policy-making and economic development. Using a multi-dimensional framework that combines normative and functional perspectives, the paper analyzes how each legal tradition contributes to shaping Nigeria’s financial systems and policy responses. Normatively, Islamic economic law emphasizes moral and ethical principles rooted in Sharia, promoting social equity and justice through instruments such as zakat and the prohibition of riba. In contrast, secular economic law prioritizes market efficiency, rationality, and individual rights, focusing on economic progress and legal certainty. Functionally, the growing success of Islamic finance—especially non-interest banking and instruments like sukuk—demonstrates its role in enhancing ethical financing and financial inclusion. Meanwhile, secular frameworks have enabled reforms such as the Banking and Other Financial Institution Act (BOFIA), improving transparency and regulatory control. This study contributes to the contextualized discourse of Islamic law by offering a nuanced analysis of how integrating ethical values from Islamic principles into Nigeria's broader legal and economic policies can foster equitable growth. It argues that recognizing both the complementary and conflicting aspects of these systems is crucial for sustainable development and for addressing Nigeria’s structural economic disparities